KERJASAMA PEMERINTAH AMERIKA SERIKAT DALAM UPAYA PENANGGULANGAN NARKOBA DI NIGERIA - Tri Laksmi, Komang (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 03 (2015), 2015)
A BS TRACT Drug trafficking is a transnational crime that is now threatening global security. Drug trafficking through Nigeria poses new challenges and exposes various threats to the United States Government. Efforts are being made by the Government of the United States to combat drug trafficking in Nigeria through the creation of West Africa Cooperative Security Initiative (WACSI) in 2011. Bilateral cooperation undertaken by the Government of the United States and Nigeria involved agencies such as the DEA, DOD, AFRICOM, and the Nigeria Police Force. This research is aimed to describe the cooperation undertaken by the United States government and Nigeria in the fight against drugs through the enforcement of WACSI. The concept used in this study is the concept of Transnational Organized Crime and Bilateral Cooperation. Keywords: Transnational Organized Crime, Bilateral Cooperation, WACSI, DEA